Influence of additives on CaCO3 precursors and multicycle CO2 capture performance of CaO sorbents. Issue 3 (June 2022) - Yue, Wenfei; Fan, Chuigang; Song, Wenli; Li, Songgeng
Abstract: Calcium looping based on alternation between uptake and release of CO2 is a promising technology for high-temperature CO2 capture. In this study, CaO sorbents were obtained from different precipitated CaCO3 precursors. Two additives, cetyltrimethyl ammonium bromide (CTAB) and triblock copolymer (P123), were used to modify CaCO3 precursors. Physical properties (morphology, crystal structure and porosity) of CaCO3 precursors, as well as CO2 capture performance of CaO sorbents were investigated. It was found that the presence of different concentration of additive would affect crystal composition and porosity of CaCO3 precursor. Experimental data showed that CaO sorbents derived from CaCO3 modified with 8 mmol/L CTAB exhibited higher CO2 capture capacity than other CaO sorbents after multiple cycles. Furthermore, the relationship between CO2 capture performance and properties of CaCO3 precursors was established. BET surface area and pore volume of CaCO3 precursors were positive correlated to average carbonation conversion. For CTAB cases, molar ratio of vaterite to calcite was negatively correlated to average carbonation conversion; and for P123 cases, molar ratio of vaterite to calcite was positively correlated to average conversion. Graphical Abstract: ga1 Highlights: Additives affected crystal composition and physical properties of CaCO3 precursor. Excellent cycle stability and CO2 capture capacity were obtained from CaO sorbent derived from CaCO3 with 8 mmol/L CTAB. BET surface area and pore volume of CaCO3 precursors were positive correlated to CO2 capture performance of CaO sorbents. Crystal composition of CaCO3 precursors modified with CTAB and P123 affected CO2 capture performance of CaO sorbents.